Pembinaan Olimpiade Sains Nasional Informatika di SMAN 2 dan SMAN 1 Jember - Rizky Alfanio Atmoko; Muhammad Andryan Wahyu Saputra; Damar Novtahaning; Narandha Arya Ranggianto; Erik Yohan Kartiko; Akbar Pandu Segara; M. Habibullah Arief (Fakultas Ilmu Komputer, Universitas Jember, 2025)
Program